HUBUNGAN ANTARA FOOD TABOO DAN KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Rifatul Imaliyah; Lirista Dyah Ayu Oktafiani; Farida Wahyu Ningtyias (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACTBackground: Factors that cause anemia in pregnancy include food taboos and adherence to taking iron tablets. The application of food taboos affects the diversity of food consumption so that it has an impact on meeting the need for iron. The Iron supplement program is a government effort to reduce the incidence of anemia in pregnancy.Objectives: This study aims to analyze the relationship between food taboos and compliance with consuming iron supplement tablets with the incidence of anemia in pregnant women.Methods: This type of research was survey research with a cross-sectional approach. A sample of 35 people from 37 pregnant women was selected using simple random sampling. Samples were randomly selected using software on a mobile phone. This research was conducted on September 5-23, 2022. In this study, food taboos and adherence to consuming iron supplement tablets were the independent variables, and the dependent variable was anemia in pregnant women. In this study, primary data included: general characteristics of the respondents (age, working status, education, distance between pregnancies, family income), food taboos and adherence to consuming iron supplement tablets. Primary data was collected by filling out a questionnaire and secondary data related to Hb in the second trimester of pregnant women was obtained from the MCH handbook. Bivariate analysis using chi square.Results: The results showed that 40.0% of the respondents who applied food taboos had anemia and 25.7% of them experienced anemia. Based on the results of the chi-square test, a p-value of 0.001 was obtained, which means that there is a relationship between food taboos and the incidence of anemia in pregnant women. 28.6% of respondents get anemia from 45.7% of respondents who were non-compliant in consuming iron-supplement tablets and the results of the chi-square test between adherence to consuming iron-supplement tablets and the incidence of anemia in pregnant women obtained a p-value of 0.001, which means there is a relationship between both;Conclusions: There is a relationship between food taboos and compliance with consuming iron supplement tablets with the incidence of anemia in pregnant women in the working area of Sukowono Public Health Center, Jember Regency.Keyword: Anemia; Food taboos; The adherenceABSTRAKLatar Belakang: Faktor penyebab anemia kehamilan diantaranya adalah food taboo dan kepatuhan mengkonsumsi tablet tambah darah. Penerapan food taboo mempengaruhi keberagaman konsumsi pangan sehingga berdampak terhadap pemenuhan kebutuhan zat besi. Program pemberian tablet tambah darah merupakan upaya pemerintah untuk menurunkan kejadian anemia kehamilan. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara food taboo dan kepatuhan mengkonsumsi tablet tambah darah dengan kejadian anemia pada ibu hamil.Metode: Jenis penelitian ini yakni penelitian survei dengan pendekatan cross-sectional. Sampel sebanyak 35 orang dari 37 ibu hamil yang dipilih menggunakan simple random sampling. Sampel dipilih secara acak dengan menggunakan perangkat lunak pada handphone. Penelitian ini dilaksanakan pada 5-23 September 2022. Dalam penelitian ini, food taboo dan kepatuhan mengkonsumsi tablet tambah darah merupakan variabel bebas (independen), serta variabel terikatnya adalah anemia pada ibu hamil. Pada penelitian ini data primer meliputi karakteristik umum responden (usia, status bekerja, pendidikan, jarak kehamilan, pendapatan keluarga), food taboo dan kepatuhan dalam mengkonsumsi tablet tambah darah. Data primer dikumpulkan melalui pengisian kuesioner dan data sekunder terkait hb ibu hamil trimester II diperoleh dari buku KIA. Analisis bivariate menggunakan chi square.Hasil: Hasil penelitian dinunjukkan dari 40% responden yang menerapkan food taboo sebesar 25,7% responden mengalami anemia. Berdasarkan hasil uji chi-square memperoleh p-value sebesar 0,001 yang artinya terdapat hubungan antara food taboo dengan kejadian anemia pada ibu hamil. Sebesar 28,6% responden mengalami anemia dari 45,7% responden yang tidak patuh dalam mengkonsumsi tablet tambah darah dan hasil uji chi square antara kepatuhan mengkonsumsi tablet tambah darah dengan kejadian anemia pada ibu hamil hamil mendapatkan p-value sebesar 0,001 yang artinya terdapat hubungan diantara keduanya.Simpulan: Terdapat hubungan antara food taboo dan kepatuhan mengkonsumsi tablet tambah darah dengan kejadian anemia pada ibu hamil di wilayah kerja Puskesmas Sukowono Kabupaten Jember.Kata Kunci : Anemia, Food taboo, Kepatuhan